Expresividad poética y traducción con breve lectura de Fedro I. 1 - Toledo Prado, Joâo Batista (Asociación Argentina de Estudios Clásicos, 2013)
The term poetic expressiveness refers to the multiple joints of the plan of expression, derived from the expressive value of the linguistic sign (ROSSET: 1970, 135) and its particular role in the field of poetry. The features of meaning, such as projection, elevation and salience, make it possible to consider expressive all poetic statements which constitute particularly dense instances in the formal consolidation of a convergence between the two planes (expression/content), and therefore it stands out from the others due to the high density of structural parallelisms and isomorphisms, which are procedures responsible for the impression that a particular form of content can only be expressed by cutting that same specific form of expression out. These considerations have an immediate impact on the reading, interpretation and practice of translating poems, which is intended to be demonstrated here, through an example of translation of a Phaedrus' fable, written in iambic meter.

El término expresividad poética se refiere a las múltiples articulaciones del plano de la expresión, derivadas del valor expresivo del signo lingüístico (ROSSET 1970: 135) y de su particular papel en los dominios poéticos. Los rasgos de significado (como proyección, elevación y relieve) permiten considerar expresivos todos los enunciados poéticos que constituyen un momento particularmente denso en la consolidación formal de la convergencia entre los dos planos (expresión/contenido); por eso se destacan de los otros por su alta densidad de paralelismos estructurales y de isomorfismos, procedimientos responsables de que uno tenga la impresión de que una forma particular de contenido sólo puede ser manifestada por el recorte determinado de una expresión específica. Estas consideraciones tienen un impacto inmediato en la lectura, interpretación y práctica de traducción de poemas, lo que se pretende aquí demostrar, a través del ejemplo de traducción de una fábula de Fedro, escrita en metro yámbico.
Keywords: Poetics of expression; Old Latin metrics; Expressiveness and poetics; Translation; Phaedrus I. 1